A study on the relationship between destination image and food image towards intention to revisit Melaka / Izyan Ainaa Izani , Noraini Mahali and Sabrena Khanum Nawab Zadah Khan - Izyan Ainaa Izani; Noraini Mahali; Sabrena Khanum Nawab Zadah Khan (Faculty of Hotel and Tourism Management, 2014)
This study aims to discover the relationship between destination image and food image towards the intention to revisit. Destination image and food image are essential that effects the tourists' destination selections. This research were conducted at Melaka and a questionaire was used to survey 50 tourists by using a convenience sampling method. The results indicated that destination image have positive relationship towards intention to revisit whereas food image does not have positive relationship toward intention to revisit.